Use of autologous fibrin glue for endoscopic treatment of esophageal lesions - Lucas, Matthias; Seeber, Petra (Endoscopy International Open, 2015)
Background and study aims: Esophageal leaks are a potentially life-threatening condition. One treatment option is injection therapy with commercially available fibrin glue. We describe herein a method to close esophageal leaks by injecting autologous fibrin glue prepared exclusively with the patient's own blood.